Homoparental families and care - Andrade-Villegas, Ángela Marcela; Uribe-López, Meggy Andrea (Prospectiva. Revista de Trabajo Social e Intervención Social, 2015)
This article outlines a reflection about care in homoparental families as a way to respond to the heteronormative pressures in the Western world, which usually disqualifies and rejects diverse families. Also, the article recognizes that family as a category of analysis has been extensively studied from different areas of knowledge and different historical moments, thereby demonstrating complex forms of family formation and remarkable changes in the collective representation of the idea of being a family. This text is an opportunity to reflect about care in homoparental families, developing on the one hand the different conceptualizations of family, the notions of primary socialization and the construction of gender identity, and on the other hand, professional reflections related to working with homoparental families.